2022
DOI: 10.1371/journal.pntd.0010219
|View full text |Cite
|
Sign up to set email alerts
|

Drug development for the treatment of onchocerciasis: Population pharmacokinetic and adverse events modeling of emodepside

Abstract: Background To accelerate the progress towards onchocerciasis elimination, a macrofilaricidal drug that kills the adult parasite is urgently needed. Emodepside has shown macrofilaricidal activity against a variety of nematodes and is currently under clinical development for the treatment of onchocerciasis. The aims of this study were i) to characterize the population pharmacokinetic properties of emodepside, ii) to link its exposure to adverse events in healthy volunteers, and iii) to propose an optimized dosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The macrofilaricidal impact of doxycycline makes it superior to moxidectin and ivermectin both of which require repeated rounds over a long period to allow macrofilaria to die. Other macrofilaricidal drugs are being developed [ 28 , 29 ] and once a better one is found, it can be used in place of doxycycline. Doxycycline is part of WHO [ 4 ] arsenal of alternative treatments and so we prefer piloting it in programme setting.…”
Section: Discussionmentioning
confidence: 99%
“…The macrofilaricidal impact of doxycycline makes it superior to moxidectin and ivermectin both of which require repeated rounds over a long period to allow macrofilaria to die. Other macrofilaricidal drugs are being developed [ 28 , 29 ] and once a better one is found, it can be used in place of doxycycline. Doxycycline is part of WHO [ 4 ] arsenal of alternative treatments and so we prefer piloting it in programme setting.…”
Section: Discussionmentioning
confidence: 99%
“…The column was monitored by UV lamp (254 and 366 nm). Fractions of 35 mL were collected as follows: [(1-6), n-hexane-EtOAc (90:10)] [ (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), n-hexane-EtOAc (8:2)], [ (25)(26)(27)(28)(29), n-hexane-EtOAc (7:3)], [ (30), n-hexane-EtOAc (6:4)], [ (31), n-hexane-EtOAc (1:1)], [ (32), n-hexane-EtOAc (4:6)], [ (33), n-hexane-EtOAc (3:7)], [ (34), n-hexane-EtOAc (2:8)] [ (35), n-hexane-EtOAc (1:9)], [(36), EtOAc-MeOH (9:1)] [(37), MeOH (100%)]. These fractions were pooled according to their TLC profiles into 10 subfractions F1 to F10 as follows: F1 (1-3; 0.05 g), F2 (4-7; 2.13 g), F3 (8-10; 0.24 g), F4 (11-13; 0.04 g), F5 (14-18; 0.04 g), F6 (19-23; 1.96 g), F7 (24-28; 0.39 g), F8 (29-31; 0.12 g), F9 (32-35; 0.06 g), and F10 (36-37; 0.39 g).…”
Section: Isolation Of Compounds 1 Andmentioning
confidence: 99%
“…Emodepside, a semisynthetic derivative of PF1022A, has shown efficacy against a variety of gastrointestinal nematodes in animals including but not limited to H. contortus (sheep), Heterakis spumosa (mice), Cooperia oncophora (cattle), and Ascaris suum (pigs) [19]. Emodepside is currently under clinical development for the treatment of onchocerciasis [20]. A study has shown that ten species of gilled fungi including the oyster mushroom Pleurotus ostreatus attack and consume nematodes [21].…”
Section: Introductionmentioning
confidence: 99%